PENGARUH KONSENTRASI REAKTAN TERHADAP KONVERSI LIMBAH PELEPAH SAWIT MENJADI ASAM LEVULINAT DENGAN METODE HIDROLISIS MENGGUNAKAN KATALIS ASAM SULFAT - Arif Kurnia; Amir Awaluddin; Edy Saputra (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Palm frond could be hydrolyzed to levulinic acid using acid catalyst. In this study,kinetics data and optimum condition of palm frond conversion to levulinic acid wasinvestigated. The conversion was conducted in ampoule as reactor (length of 150 mm,I.D. of 4 mm and O.D. of 7 mm) over the following range of condition: palm frondconcentrations of 1-5 wt% (1-5 g/100 mL), temperature of 190 o C, sulfuric acidconcentrations of 1 M, and residence times of 0-240 min. The maximum LA yield isapproximately 9,38% (based on biomass weight) and 31,28% (based on celluloseweight) was achieved for an initial palm frond concentration of 1 wt% (w/v), acidconcentration of 1 M, temperature of 190 o C, and residence time of 60 min. The resultshowed that the concentration and yield of levulinic acid was affected by palm frondconcentration, but didn’t affect reaction rate.